Physico Chemical Characteristic of Kappa Carrageenan Degraded Using Hydrogen Peroxide - Rizky Febriansyah Siregar; Joko Santoso; Uju Uju (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractKappa carrageenan is polysaccharide that widely used in food, pharmaceutical, cosmetic, textile and printing industries as coagulate agent, stabilizer and gelling agent. Hydrogen peroxide (H2O2) is strong oxidator to degrade polysaccharide. Hydrogen peroxide has some advantades such as cheap, easy to get and savety environment. Degradation method using hydrogen peroxide is a technology based on establishment radical hydoxile reactive that attack the glycosidic of polysaccharides as a result reducing in molecular weight of polysaccharide. The aims of this study were to analyze the effect of hydrogen peroxide concentration, temperature and degradation time to molecular weight of refined kappa carrageenan. Structural changes on kappa carrageenan degradation were characterized by viscometer, SEM and FTIR. Hydrogen peroxide concentration, temperature and degradation time were significantly reducing molecular weight and changes in the structural function of refined kappa carrageenan. The lowest molecular weight of refined kappa carrageenan degraded was obtained from the treatment 3% of hydrogen peroxide at temperature 80°C and degradation time for 4 hours.